2006
DOI: 10.1080/08039480600636494
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions of antidepressants and antipsychotics: Experience, knowledge and attitudes among Norwegian psychiatrists

Abstract: Efficient prevention of adverse drug reactions (ADRs) requires knowledge about their severity and pharmacological mechanisms and is dependent on reliable data on their frequencies and possible risk factors. The study was conducted to investigate the prescribers' experience and understanding of the ADRs of psychotropic drugs, and their attitude towards reporting these. In a questionnaire, physicians treating adult psychiatric patients were asked which ADRs that they regarded bothersome for some of the most wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[9] A knowledge, attitude and practice based study conducted in Norway found that ADRs can be prevented by collecting reliable information about their frequencies and possible risk factors. [10] In our study, which is based on active surveillance rather than spontaneous reporting, we found antipsychotics to be most commonly responsible; this could be partly related to the frequency and duration of their use in the hospital setting.…”
Section: Discussionmentioning
confidence: 85%
“…[9] A knowledge, attitude and practice based study conducted in Norway found that ADRs can be prevented by collecting reliable information about their frequencies and possible risk factors. [10] In our study, which is based on active surveillance rather than spontaneous reporting, we found antipsychotics to be most commonly responsible; this could be partly related to the frequency and duration of their use in the hospital setting.…”
Section: Discussionmentioning
confidence: 85%
“…A knowledge, practice and attitude based study conducted in Norway found that ADRs can be prevented by collecting reliable information about their frequencies and possible risk factors. [15] Spontaneous reporting is the most common method used in pharmacovigilance and is the best one to generate signals on new or rare ADRs. Under reporting is a major drawback of this system due to lack of awareness both at the level of healthcare professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Castberg et al (2006) studied the understanding of Acute Drug Reactions (ADR) and noted that psychiatrists reported bothersome ADR's occurred 2.4 to 9.3 times and to practitioners more than residents. Knowledge about the association of receptor site blockade with a specific ADR, varied from 37% to 76% of respondents.…”
Section: Studies Of Sleep Loss In the Clinical Situationmentioning
confidence: 99%